PENGARUH LINGKUNGAN KERJA DAN KOMUNIKASI INTERPERSONAL TERHADAP KEPUASAN KERJA KARYAWAN PADA PT CAHAYA DIDIK DI JAKARTA - Chintya Magdalena; Abbas Mansyur (JAMBIS : Jurnal Administrasi Bisnis, 2022)
The research objective is to analyze the Influence of Working Environment and Interpersonal Communication toward Employee Job Satisfaction in PT.Cahaya Didik partially and simultaneously. This research uses quantitative research with quantitative descriptive approach. The analysis technique uses multiple linear regression analysis. Data analysis used the IBM SPSS Statistics Version 24 program. The study population was employees of the PT.Cahaya Didik, amounting to 30 people, using the Census obtained 20 samples. The results of the study: (1) There is a positive and significant Influence of Working Environment toward Employee Job Satisfaction in the PT.Cahaya Didik, with magnitude of influence 46%. (2) There is a positive and significant Influence of Interpersonal Communication toward Employee Job Satisfaction in PT.Cahaya Didik, with magnitude of influence 67.5%. (3) There is a positive and significant Influence of Working Environment and Interpersonal Communication simultaneously toward Employee Job Satisfaction in PT.Cahaya Didik, the magnitude of influence of the remaining 77% by 23% is influenced by other factors not examined.